HERMENEUTIKA HANS-GEORG GADAMER DAN SIGNIFIKANSINYA TERHADAP PENAFSIRAN AL-QURAN - Muh. Hanif (MAGHZA, 2017)
The paper discusses the introduction of hermeneutics, Gadamer's biography, Gadamer's hermeneutics and Quranic exegesis, and examples of interpreters using the Gadamer hermeneutics model. hermeneutics tried to grasp the meaning of the Quranic text. Meaning comes from the German "Meinen" which means "to be in the mind or right." Meanings are produced on the basis of a fusion of horizon or a mixture of the author's horizon of thought, reader, and text. interpretation is a productive act involving the subjectivity of the interpreter and is influenced by the historical reality and the presupposition of the interpreter. Gadamer hermeneutics is widely applied in the way of interpretation of the Qur'an bi al-ra'yi.